Removal of suspended solids and residual oil using membrane separation technology - Ibrahim, Norliza; Ahmad, Abdul Latif; Bhatia, Subhash (2004)
The application of membrane separation technology can be an effective means of treating palm oil mill effluent (POME). Palm oil mill effluent was first pretreated to remove the high content of suspended solids and residual oil. The pretreatment process has three stages of separation. The first stage was removal of suspended solids using flocculation while the second and third stages were removal of residual oil using solvent extraction and adsorption respectively. These three stages were important in reducing membrane fouling at the membrane separation process. Membrane separation was subsequently applied to remove any residual suspended solids and oil remaining after the pretreatments. Several operating conditions such as membrane type, pH and pressure were varied to find the optimum conditions for membrane separation process. The treatment efficiency of the process was measured as percentage removal of suspended solids and oil respectively. It was found that, in membrane separation process, GH and CE(GH) membrane gave 63% and 49% reduction in suspended solids and residual oil respectively at pH 9 and pressure of 1000 kPa.